Career success : a study of M.Sc. HRD graduates in UNIMAS - Fiona, Fan (2009)
The aim of the study is to explore the perception of M.Sc. HRD graduates toward career success, specifically the reason for taking a M.Sc. HRD degree, and differences in the perception of M.Sc. HRD graduates on career success based on gender, age and ethnic origin / race. This may be attributed to the respondents’ expectation that knowledge and skills obtained through education will lead to improvements in work outcomes such as increased pay, recognition, and opportunities (Naquin & Holton, 2003). The inconsistencies in the findings of the study compared to past similar studies may be due to the fact that the study was built on external sources instead of in the Malaysian context.